Determination of the intracellular concentration of the export chaperone SecB in Escherichia coli. - Bahar T Findik; Linda L Randall (PLoS ONE, 2017)
SecB, a small tetrameric chaperone in Escherichia coli, plays a crucial role during protein export via the general secretory pathway by binding precursor polypeptides in a nonnative conformation and passing them to SecA, the ATPase of the translocon. The dissociation constants for the interactions are known; however to relate studies in vitro to export in a living cell requires knowledge of the concentrations of the proteins in the cell. Presently in the literature there is no report of a rigorous determination of the intracellular concentration of SecB. The values available vary over 60 fold and the details of the techniques used are not given. Here we use quantitative immunoblotting to determine the level of SecB expressed from the chromosome in E.coli grown in two commonly used media. In rich medium SecB was present at 1.6 ± 0.2 μM and in minimal medium at 2.5 ± 0.6 μM. These values allow studies of SecB carried out in vitro to be applied to the situation in the cell as SecB interacts with its binding partners to move precursor polypeptides through the export pathway.